Legal Aspects of Licensing by Adhesion and Commitment (LAC) - Juliano Heinen (Revista de Direito Econômico e Socioambiental)
The present paper intends to analyze the legal aspects of Environmental Licensing by Commitment (LAC), from the constitutional and legal provisions on the subject. Therefore, the conceptual bases of the institute and its purpose are exposed. Then, faced with the problems brought to the Judiciary, notably to the Federal Supreme Court, two questions are answered: the LAC is constitutional, even if provided for by a municipal or state normative act, as well as what are the requirements to implement it. The deductive and exploratory method was applied to reach the conclusions presented at the end.